Review of the Actuarial Forecasts of the Proposed Contributory Social Security Regime in Timor-Leste - World Bank (Jakarta, 2015)
This report briefly summarizes the results for the analysis of the design, financing and administrative processes for a national social security system covering all salaried workers in Timor-Leste, including analysis of the actuarial report (ACL Report) prepared for the Directorate General of Social Security by its consultant. The report is divided into seven sections: (i) Scope of Work; (ii) ACL Report Assumptions and Methods Comment; (iii) ACL Plan Design Comments; (iv) PROST Analysis: ACL Report Design, Assumptions and Methods; (v) PROST Analysis: ACL Report Design, Bank Assumptions and Methods; (vi) Social Security Pension Fund Establishment; and (vii) Conclusion. In the final analysis it was determined that the ACL report does not meet international standards for actuarial reports for national social insurance systems. Furthermore it misrepresents the long-term costs of the proposed Timor-Leste national social security system by using non-standard assumptions and methods and an unusually short analysis period. It is suggested that the government of Timor-Leste carefully consider all aspects of design and funding before adopting the new system, as the decisions made will have very significant macroeconomic, labor market, budget, and social policy implications for the country for decades to come.